Combined loading capacity of skirted circular foundations in loose sand. (1st July 2019) - Fiumana, Nicole; Bienen, Britta; Govoni, Laura; Gourvenec, Susan; Cassidy, Mark J.; Gottardi, Guido
Abstract: Skirted foundations are an attractive foundation concept in the offshore energy sector, both for wind turbines and oil and gas platforms. Most of the evidence of skirted foundation behaviour under combined vertical, horizontal and moment (VHM) loading in sand has been collected from small-scale model experiments conducted at unit gravity on the laboratory floor. This paper presents results from a series of centrifuge experiments of skirted foundations on loose silica sand at relevant prototype stress levels. The vertical load-penetration curve is shown to be predicted well using established analytical methods. Centrifuge modelling results provide experimental evidence of the complex effects of the interaction of skirt aspect ratio and relative stress level on the VHM yield surface. A conservative and design-oriented solution based on the yield envelope approach describes available foundation capacity within the established framework of strain-hardening plasticity theory.